2020
DOI: 10.3390/polym12030541
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Crystallization Promotion Effect of Montmorillonite on PTT/PC Blends with PTT as the Continuous Phase

Abstract: To regulate the crystallization of poly(trimethylene terephthalate) (PTT) retarded by melt blending with polycarbonate (PC), the crystallization of the PTT/PC blend was investigated employing nano-montmorillonite (MMT) as a crystallization promoter with PTT as the continuous phase. The results showed that MMT exhibits a significant promoting effect on PTT crystallization; the presence of 1 wt. % MMT shifts the initial and peak crystallization temperatures of the 70/30 PTT/PC blend to ~17 °C and ~32 °C, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They demonstrated that adding MMT with strong nucleation activity might lower the crystallization activation energy of iPP while increasing its crystallization rate. By using MMT as a crystallization aid (MMT content: 1 wt%), Xue et al investigated the crystallization behavior of PTT/PC blends [ 28 ]. They discovered that uniformly exfoliated and distributed MMT contributed considerably to the crystallization of PTT.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that adding MMT with strong nucleation activity might lower the crystallization activation energy of iPP while increasing its crystallization rate. By using MMT as a crystallization aid (MMT content: 1 wt%), Xue et al investigated the crystallization behavior of PTT/PC blends [ 28 ]. They discovered that uniformly exfoliated and distributed MMT contributed considerably to the crystallization of PTT.…”
Section: Introductionmentioning
confidence: 99%
“…Montmorillonite (MMT) is one such form of nanoclay phyllosilicate mineral possessing one O–Al(Mg)–O octahedral sheet sandwiched between two O–Si–O tetrahedral sheets [ 13 ]. MMT-based polymer nanocomposites have been under constant scrutiny in recent years owing to its high aspect ratio, cation exchange capacity, superior surface area, and small particle size [ 14 ]. However, MMT reinforcement within a polymer matrix suffers certain impediments in the form of agglomeration which influences the dispersion and exfoliation of MMT in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%